Melampaui Prokreasi: “Keturunan Ilahi” (זֶרַע אֱלֹהִים) sebagai Telos Perjanjian Pernikahan dalam Maleakhi 2:13-16 - Wennar (Sekolah Tinggi Teologi Sriwijaya, 2025)
This study analyzes the controversial phrase “divine offspring” (זֶרַע אֱלֹהִים, zeraʿ ʾĕlōhîm) in Malachi 2:15. Contrary to the common interpretation that only understands it as the biological procreation of children, this study argues that “divine offspring” is the telos (theological ultimate goal) of the marriage covenant itself. Using exegetical methods that focus on the lexical-syntactic analysis and the literary-historical context of Malachi 2:13-16, this article shows that divorce and infidelity are not only seen as violations of the social contract, but as acts that fundamentally sabotage God’s purpose of creating a godly and faithful covenant community. Divorce, for Malachi, is violence (חָמָס, ḥāmās) that destroys the foundation on which the “divine seed”—the generation living in obedience to Yahweh—can be raised. Thus, as will be shown, the stability of faithful monogamous marriage is not an end in itself, but rather an essential prerequisite for the fulfillment of the larger divine mandate for the post-exilic people.